The frequency of assessment of progression in randomized oncology clinical trials. Issue 7 (24th November 2021) - Haslam, Alyson; Gill, Jennifer; Prasad, Vinay
Abstract: Background: Progression in tumor assessments is often detected at a follow‐up appointment rather than when actual change in progression has occurred, which can bias PFS outcomes. Aim: We sought to evaluate the frequency of tumor assessment scans in clinical trials of anti‐cancer interventions and to compare this to recommended (National Comprehensive Cancer Network) and real‐world frequencies of tumor assessments. Methods: In a cross‐sectional analysis, we searched for articles published in the three top oncology journals between July 2017 and June 2020. We included articles that were RCTs of patients that had unresectable or metastatic solid tumors and used an intervention that was designed to be anti‐tumor. We abstracted median PFS survival for each group, the PFS hazard ratio, frequency of tumor assessment scans, tumor type, intervention type, and information regarding the study. Results: We found that, in the 182 comparisons (163 articles), less frequent tumor assessment (occurring more than 9 weeks between assessments) was associated with higher median PFS values for both the intervention group ( p  < .0001) and the control group ( p  < .0001). PFS hazard ratios for studies scanning for tumors every 10 or more weeks were no different than for studies scanning for tumors more frequently ( p  = .88). Data on the frequency of tumor assessments in the real world is sparse. Conclusion: We found that less frequent tumor assessment frequency was associated with longer median PFS in both intervention and control groups of clinical oncology trials but was not associated with differences in PFS hazard ratios. Future research is needed to compare real world to trial assessment.